Meningkatkan Motivasi Belajar Peserta Didik melalui Program Lestari Belajar di PKBM Gema Kota Tasikmalaya - Vania Alisa Fujianti; Nena Siti Mutmainah; Vida Zahrotun Baeturohmah; Raisya Nurfajria; Desti Oktaviatien Wijaya; Fathia Nabila Farhana; Lilis Karwati (Departement of Mathematics Education, 2024)
Learning motivation is an important factor in the success of education, especially for students at the Community Learning Activity Center (PKBM). However, low learning motivation is often an obstacle in achieving optimal learning outcomes. This study aims to improve the learning motivation of Package B students through the Lestari Belajar program at PKBM Gema Tasikmalaya. This program is designed to improve knowledge, skills, learning motivation and create a conducive and interesting learning environment. The methodology used is a quantitative method with a survey design type to obtain data systematically from respondents where data is collected through questionnaires. The Lestari Belajar program has succeeded in increasing the learning motivation of students at PKBM Gema, as indicated by a significant increase in the results of learning motivation measurements after the program is implemented. These findings indicate that a relevant and participatory educational approach is able to create an interesting learning environment and support learning motivation.